Crosstalk freeness of concatenated modified plus-minus 2i photonic switching network - Rahman, M.M. Hafizur; Manjur, S.M. Ashif; Patwary, A.B.M. Kowser; Inoguchi, Yasushi (2014)
In this paper, we analyze the crosstalk freeness Concatenated Modified Plus-Minus 2i (CMPM2I) photonic switching network. A new routing algorithm is proposed for this network, which decomposes a permutation into two semi-permutations. It is shown that using the proposed routing algorithm the CMPM2I network is capable of realizing semi-permutation in one pass and thus the whole network is corsstalk free in two passes.